Grievances and rebellion: Comparing relative deprivation and horizontal inequality. (November 2020) - Siroky, David; Warner, Carolyn M.; Filip-Crawford, Gabrielle; Berlin, Anna; Neuberg, Steven L.
Social science answers to the essential question of group conflict have focused on two main explanations—their motivating "grievances" and their mobilization "capacity" for collective action. Recent years have seen a renewed focus on grievances in the form of horizontal inequalities (between-group inequality), but the important conceptual and potential empirical differences between horizontal inequality and relative deprivation have not yet been incorporated into this discussion fully. This article first discusses these distinctions, and then assesses how they influence collective violence using new global evidence. Consistent with the theoretical discussion, the empirical results indicate that these concepts are not substitutes, and indeed are only weakly correlated, but rather tap into distinct aspects of grievance. The paper discusses the implications of these results, validates them in a series of robustness checks, and concludes with possible extensions along with future directions.